2015
DOI: 10.1007/s11999-015-4460-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Cup-cage Reconstruction With Oversized Cups Provide Initial Stability in THA for Osteoporotic Acetabular Fractures?

Abstract: Background The incidence of acetabular fractures in osteoporotic patients is increasing. Immediate total hip arthroplasty (THA) has potential advantages, but achieving acetabular component stability is challenging and, at early followup, reported revision rates for loosening are high. Questions/purposes This study measured acetabular component stability and the initial surface contact achieved between the acetabular component and unfractured region of the pelvis after THA using an oversized acetabular componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…However, to our knowledge there are only four studies that investigated the association between early migration of the femoral component in THAs and stem survival [11,14,17,19]. Whereas early migration measurement is commonly recommended as a valuable tool to detect unsafe and poor-performing implants early and to prevent their widespread use [16,30], there is a lack of studies that correlate early migration and late implant loosening in the same patient cohort, particularly regarding long-term observations ([ 10 years) [36]. Furthermore, and even more important, none of these previous studies [11,14,17,19] investigated this relationship exclusively for cementless femoral stems.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge there are only four studies that investigated the association between early migration of the femoral component in THAs and stem survival [11,14,17,19]. Whereas early migration measurement is commonly recommended as a valuable tool to detect unsafe and poor-performing implants early and to prevent their widespread use [16,30], there is a lack of studies that correlate early migration and late implant loosening in the same patient cohort, particularly regarding long-term observations ([ 10 years) [36]. Furthermore, and even more important, none of these previous studies [11,14,17,19] investigated this relationship exclusively for cementless femoral stems.…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular fractures should be considered separately as they involve the hip joint; thus, unless there is minimal displacement and hip joint stability, surgical treatment is proposed: absolute operative indications include open fractures, hip joint instability and intra-articular loose bodies; hip joint incongruity and intra-articular displacement exceeding 2 or 3 mm may also be considered for surgery because of the early arthritis risk [15]. Studies [26,27] on technical aspects on this surgery have been recently published to try to improve the surgical benefit. In summary, the large majority of pelvic fractures do not require surgery, except acetabular fractures.…”
Section: Treatmentmentioning
confidence: 99%
“…Nowadays, with modern protrusion cages, the semielliptical cups, the mobility and the new double-coated hydroxyapatite femoral stems, the implant failure is very difficult, if not rare. Moreover, this implant can have a long life as a primary THA osteoarthritis implant [22][23][24][25][26][27]. In the literature, it is shown that the prosthesis in acetabular fracture outcomes has a higher bleeding compared to THA and ORIF in acute trauma [1,28].…”
Section: Discussionmentioning
confidence: 99%